1983
DOI: 10.1258/002367783781062307
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of members of the Pasteurella-Actinobacillus-group from guineapigs

Abstract: In the course of post-mortem bacteriological examination of conventional guineapigs, 88 isolates belonging to the Pasteurella-Actinobacillus-group were recovered from 69 of 279 animals (25%). Most isolates were recovered from pneumonic lung, enteritic jejunum and inflamed mammary gland. No relationship was found between biotype and source of isolation. About 50% of isolates were recovered in pure culture or as the predominant micro-organism. It is concluded that members of the Pasteurella-Actinobacillus-group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…24,25 Boot and colleagues (1983) concluded that the Pasteurella and Actinobacillus genera belonging to the Pasteurellaceae must be considered as potentially pathogenic microorganisms for guinea pigs. 26 The statistically higher STT-II and prevalence of mucopurulent discharge indicating ocular discomfort in our Skinny pigs with a higher representation of ocular abnormalities (chemosis/hyperemia of the conjunctiva, trichiasis, keratitis with corneal vascularization, foreign body) compared to haired guinea pigs suggests that the commonly isolated Pasteurellaceae in Skinny pigs may be considered pathogenic. Only 2 out of 20 eyes of the haired guinea pigs were positive for Pasteurella ceae (one was an unspeciated Pasteurellaceae , and the other was Mannheimia caviae ) and both eyes showed ocular abnormalities.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…24,25 Boot and colleagues (1983) concluded that the Pasteurella and Actinobacillus genera belonging to the Pasteurellaceae must be considered as potentially pathogenic microorganisms for guinea pigs. 26 The statistically higher STT-II and prevalence of mucopurulent discharge indicating ocular discomfort in our Skinny pigs with a higher representation of ocular abnormalities (chemosis/hyperemia of the conjunctiva, trichiasis, keratitis with corneal vascularization, foreign body) compared to haired guinea pigs suggests that the commonly isolated Pasteurellaceae in Skinny pigs may be considered pathogenic. Only 2 out of 20 eyes of the haired guinea pigs were positive for Pasteurella ceae (one was an unspeciated Pasteurellaceae , and the other was Mannheimia caviae ) and both eyes showed ocular abnormalities.…”
Section: Discussionmentioning
confidence: 76%
“…Unclassified Pasteurellaceae isolates have been identified in a case of putrid conjunctivitis but also in an epidemic outbreak of conjunctivitis in a large group of guinea pigs . Boot and colleagues (1983) concluded that the Pasteurella and Actinobacillus genera belonging to the Pasteurellaceae must be considered as potentially pathogenic microorganisms for guinea pigs . The statistically higher STT‐II and prevalence of mucopurulent discharge indicating ocular discomfort in our Skinny pigs with a higher representation of ocular abnormalities (chemosis/hyperemia of the conjunctiva, trichiasis, keratitis with corneal vascularization, foreign body) compared to haired guinea pigs suggests that the commonly isolated Pasteurellaceae in Skinny pigs may be considered pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Finally, a group of isolates labelled "Avian INTRODUCTION In the Approved Lists of Bacterial Names (Skerman et al, 1980) five species of the genus Actinobacillus Brumpt 1910 and six species of Pasteurella Trevisan 1887 were recognised. Several other named or unnamed Pasteurella or Actinobacillus species were not included in the Lists, or have been described afterwards (Simpson and Simmons, 1980;Friis-M^ller, 1981;Frederiksen, 1981;Bisgaard, 1982;Snipes and Biberstein, 1982;Bisgaard et al, 1983;Boot et al, 1983;Pohl et al, 1983). According to Biberstèin (1981) the species constituting the genera Pasteurella and Actinobacillus represent a biotypic continuum of many intergrading forms with no dependable boundaries between species and even genera.…”
Section: Discussionmentioning
confidence: 99%
“…The inbred colony, the production of which gradually replaced initially imported animals, housed 50 breeding females on average and showed a similar mortality rate. In both colonies a variety of common bacterial pathogens was present as has been described earlier for the random-bred colony (Boot, Oosterom & Walvoort, 1983).…”
Section: Sources and Methods Of Isolationmentioning
confidence: 84%